Perencanaan Arsitektur Sistem Informasi Persediaan Menggunakan Metode EAP di BULOG Subdivre Bandung - Muhamad Fahmi Nugraha; Anjas Tryana; Tita Novita (INTERNAL (Information System Journal), 2023)
Information system planning becomes the most important role to support technological advances in the future. The planning made is regarding the inventory and financial information system in accordance with the problems that exist in BULOG Subdivre Bandung. The purpose of this research is to make information system architecture planning at BULOG Sub Dirve Bandung using the Enterprise Architecture Planning method. The model that will be used in the enterprise architecture is the Enterprise Architecture Planning (EAP) model. This definition of enterprise architecture focuses on data, application, and technology architectures to support business functions and the plans to be implemented on that architecture. The results of the research carried out are blueprints in the form of recommendations for inventory and financial information systems at BULOG Subdivre Bandung, which produce 3 main business processes, in data architecture it produces 15 entities, and 4 applications and for technology architecture, which produces technology proposals that will be used in the future. will come.